Carbon–carbon double-bond reductases in nature. (August 2014) - Huang, Minmin; Hu, Haihong; Ma, Li; Zhou, Quan; Yu, Lushan; Zeng, Su
Abstract Reduction of C = C bonds by reductases, found in a variety of microorganisms (e.g. yeasts, bacteria, and lower fungi), animals, and plants has applications in the production of metabolites that include pharmacologically active drugs and other chemicals. Therefore, the reductase enzymes that mediate this transformation have become important therapeutic targets and biotechnological tools. These reductases are broad-spectrum, in that, they can act on isolation/conjugation C = C-bond compounds, α, β-unsaturated carbonyl compounds, carboxylic acids, acid derivatives, and nitro compounds. In addition, several mutations in the reductase gene have been identified, some associated with diseases. Several of these reductases have been cloned and/or purified, and studies to further characterize them and determine their structure in order to identify potential industrial biocatalysts are still in progress. In this study, crucial reductases for bioreduction of C = C bonds have been reviewed with emphasis on their principal substrates and effective inhibitors, their distribution, genetic polymorphisms, and implications in human disease and treatment.